Intelligent CRM on the cloud - Faed, Alireza; Wu, Chen; Chang, Elizabeth (IEEE Computer Society, 2010)
This paper presents a new conceptual framework and practical solution for Customer Relationship Management(CRM) and E-Loyalty programs for cutting edge M-Commerce. CRM has come to the world of technology to help companies maximise technology usage. CRM means disciplined business strategy to create and sustain long-term, profitable customer relationships. To this aim, it must concentrate on customer. This paper introduces the notion of Intelligence CRM (i-CRM), and will define and develop i-CRM, E-Loyalty for the M-Commerce environment including Cloud services. The conceptual framework will include solutions for customer complaints and evaluation of the solution through perceived value, interactivity, and acceptance of i-CRM, perceived ease of use, perceived usefulness, loyalty and E-Loyalty. This paper shows how i-CRMcan foresee the threshold of customer feedback creating an innovative solution to minimize negative customer feedback and increase the loyalty and E-Loyalty of an organization.